Temperature dependence of luminescence pecularities in oxygen doped ZnTe films - Malushin, N.V.; Skobeeva, V.M.; Smyntyna, V.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2003)
Temperature dependence of luminescence intensity inherent to zinc telluride films prepared by the method of vacuum deposition and containing an oxygen impurity was investigated. The model explaining non-monotonous behaviour of curve temperature dependence for the "oxygen" band (λmax = 650 nm) is offered. According to this model, during quenching luminescence, the centers of a luminescence and those of the majority carriers capture participate. Determined are the values of the activation energy and concentration of the appropriate centers at which abnormal dependence of luminescence intensity on the temperature is observed.